Spontaneous and activation-induced apoptosis of peripheral blood mononuclear cells in the pathogenesis of type 1 diabetes mellitus - A. V. Lugovaya; N. M. Kalinina; V. Ph. Mitreikin; Yu. V. Emanuel; Yu. P. Kovalchuk; A. V. Artyomova (Медицинская иммунология)
Apoptosis is the leading mechanism of pancreatic β-cell destruction in type 1 diabetes mellitus (T1DM). Assessment of activation apoptosis in response to stimulation with mitogen or a specific antigen is considered more significant when studying apoptosis markers in peripheral blood mononuclear cells to clarify the role of programmed cell death in pathogenesis of various diseases, since the role of apoptosis in immune response is increased in activated cells. It has been established that the stimuli that activate resting Tlymphocytes initiate apoptotic death of activated T lymphocytes. Therefore, detection of spontaneous apoptosis only is not very informative. In addition, determination of cell sensitivity to apoptosis induction makes it possible to identify relations of pathological process to the enhancement or weakening of this sensitivity. The key point in the T1DM initiation is apoptosis resistance of activated autoreactive T lymphocytes, that migrate from bloodstream to the pancreas and take an active part in destruction of the pancreatic insular structures. Despite long studies of T1DM pathogenesis, the exact causes of resistance of effector T cell clones to apoptosis remain unclear. There are no facts that answer the question: to what extent is the ability of T lymphocytes of peripheral blood to enter into apoptosis associated with severity and duration of the disease. In this regard, the aim of the study was to evaluate the effectiveness of in vitro activation-induced apoptosis of T lymphocytes in the patients with T1DM, depending on the state of compensation and duration of the disease. The features of activationinduced apoptosis have been studied in cultures of peripheral blood mononuclear cells (PBMC) in the patients with T1DM. Phytohemagglutinin (PHA) and insulin were used as apoptosis inducers. Increased in vitro sensitivity of PBMC to activation-induced apoptosis was revealed in T1DM patients. The strongest apoptotic response to PHA was detected in cases of T1DM decompensation. Considering predominantly Tcells to undergo apoptosis in response to PHA stimulation, one may speak about high sensitivity of activated T lymphocytes to induced apoptosis in the patients with T1DM. The highest level of activation-induced apoptosis in response to insulin stimulation was revealed in the compensation phase of T1DM. We have found that the intensity of spontaneous and activation-induced apoptosis correlates with decompensation of the disease and the degree of β-cells secretory function disorder. In fact, strong direct correlation was observed between the percentage of hypodiploid cells and blood concentration of glucose, and the inverse correlation was shown between the number of apoptotic cells and serum levels of C-peptide. The data obtained are in accordance with the modern concept of T1DM immunopathogenesis, which includes a development of autoimmune diseases associated not only with enhanced apoptosis of target cells, but also with a defect in phagocytic clearance of apoptotic cells due to impaired efferocytosis, i.e., phagocytosis of apoptotic cells. Thus, the maximal increase in spontaneous and activation-induced apoptosis levels of peripheral blood lymphocytes during the DM-1 decompensation is explained not only by the hyperglycemia effects, but also by the secondary immune response to the so-called “late apoptotic” or “secondary necrotic” β-cells, due to their ineffective phagocytic clearance.